Medium-chain acyl-CoA dehydrogenase deficiency in North Macedonia – ten years experience - Anastasovska, Violeta; Kocova, Mirjana; Tesovnik, Tine; Zdraveska, Nikolina; Debeljak, Maruša; Kovač, Jernej (Walter de Gruyter GmbH, 2025)
Objectives Medium-chain acyl-CoA dehydrogenase deficiency (MCADD) is an autosomal recessive disorder of fatty acid oxidation, with potentialy fatal outcome. Early diagnosis of MCADD by acylcarnitine analysis on newborn screening using tandem mass spectrometry can potentially reduce morbidity and mortality. In this study, we evaluate the prevalence and genetic background of MCADD in North Macedonia. Methods Medium chain length acylcarnitines, were measured on newborn screening blood spot cards by tandem mass spectrometry. The molecular diagnosis was performed by whole exome sequencing of the ACADM gene, and detected mutations were confirmed with Sanger sequencing in all neonates with positive MCAD screening markers, and their parents as well. Results A total of 52,942 newborns were covered by metabolic screening during the period May 2014–May 2024. 11 unrelated Macedonian neonates were detected with positive MCADD screening markers, and prevalence of 1/4,813 live births was estimated. Molecular analysis of the ACADM gene showed that c.985A>G was the most prevalent mutation occurred on 77.27 % of the alleles, while 18.18 % alleles carried c.244dupT pathogenic variant. Seven patients were homozygous for c.985A>G (63.6 %) while one was homozygous for c.244dupT (9.1 %) variant. Two patients were compound heterozygotes with c.985A>G/c.244dupT genotype (18.2 %), and one patient had c.985A>G allele without detection of the second ACADM mutant allele. Conclusions The NBS estimated prevalence of MCADD in Macedonian population was more frequent than in the other European population and worldwide incidence in general. This is the first report of the genetic background of MCADD in North Macedonia.